PENGARUH MEDIA GAMBAR TERHADAP HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Oktapianti, Desti; Tarpan Suparman; Yayan Alpian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Science plays a crucial role in arousing students' curiosity about the phenomena around them. However, monotonous learning methods can reduce student participation, which has an impact on low science learning outcomes. This research aims to evaluate the effect of using image media on science learning outcomes, especially material on the human respiratory system, in class V at SDN Palumbosari IV. This research applies a descriptive quantitative approach with a Pretest Post-test Nonquivalent Control Group experimental design. The sample consisted of class V students at SDN Palumbonsari IV who were chosen randomly, with class VA as the conventional learning control group and class VB as the image media experimental group. The research instrument is a multiple choice test that has been validated and tested on participants outside the sample. Data were analyzed using normality, homogeneity and hypothesis testing with the Paired Samples Test. The results of the analysis show significant differences between the average student learning outcomes before and after treatment. Students who receive learning using image media show a more significant increase in science learning outcomes compared to students who take part in conventional learning. In conclusion, the use of image media in science and science learning is effective in improving student learning outcomes, making the learning process more meaningful, enjoyable, and encouraging student activity”.